Intersection of Animated Films, Religious Education, and Parenting: A Phenomenological Study (THUFULA, 2023)
Parents introduce electronic screens to children because they are busy, want to provide religious viewing, and hope to develop children’s imagination. Then this study aims to dig deeper into the intersectionality of religious animated films that children watch, educational values, and parenting styles. This study chose a phenomenological study to analyze these social practices. Informants are parents who interpret children’s religious animated films as a system of positive norms, rules, and values. Nine groups of husband and wife became research informants. Interviews were used to obtain data which was analyzed according to the parents’ interpretive categories. Data representation is formed through the experiences and values that the informants believe. Interpretive conclusions come from data reductions obtained from informants and present research results away from the value bias that researchers believe. The reasons for the values parents feel toward children’s religious animated films are explained further in the study.